Protokol Komunikasi untuk Aplikasi Monitoring Distribusi Obat Psikotropika dengan Transmisi Data melalui Internet - Muhammad Bilda Kusuma (Politeknik Negeri Malang, 2017)
One of the problems associated with the distribution of psychotropic drugs is that there is a lot of abuse and smuggling because of the lack of supervision. Therefore, it is necessary to make a supporting application, namely the application of monitoring the distribution of psychotropic drugs by transmitting data via the internet. By utilizing NFC technology on smartphones, Delphi programming, PHP, and also the MySQL database, an application is made to function as a system. Making this application is done using the Delphi 7 application as a user application and the Notepad ++ application to build a security web that is connected to the database on localhost phpmyadmin for data delivery monitoring the distribution of psychotropic drugs. From the test results of this application, the results of the application performance test run well as expected, and encrypted URLs can only be logged if there is a validation process with a database server, supported by an NFC tag system that has a reading distance of 3 cm proves that the application security system is good.